Pengaruh Motivasi Kerja, Disiplin Kerja, dan Lingkungan Kerja terhadap Kinerja Karyawan PT. Bumi Alam Segar Kota Bekasi - Aisyah Nurrizki; Eri Bukhari; M. Fadhli Nursal (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
This research aims to determine whether there is an influence of work motivation, work discipline and work environment on the performance of PT employees. Fresh Natural Earth Bekasi City. This type of research is quantitative. The population in this study were employees of PT. Bumi Alam Segar numbered 386 with a sample of 80 respondents. The data collection technique is by distributing questionnaires. Hypothesis testing in this research uses Multiple Linear Regression analysis. The results of this research show that: (1) Work Motivation has a positive and significant effect in partial tests on Employee Performance of 2.504 > 1.99167 and a significance value of 0.014 < 0.05. (2) Work Discipline has a positive and significant effect in a partial test on Employee Performance of 4.064 > 1.99167 and a significance value of 0.000 < 0.05. (3) The work environment does not have a positive and significant effect in the partial test on employee performance of 1.912 < 1.99167 and a significance value of 0.060 > 0.05. (4) Work Motivation, Work Discipline and Work Environment have a positive and significant effect in a simultaneous test on Employee Performance of 49.707 > 2.72 and a significance value of 0.000 < 0.05.